An Investigation of the Impact of a Flipped Classroom Instructional Approach on High School Students’ Content Knowledge and Attitude Toward the Learning Environment. - Bell, Matthew; Shumway, Steven; Wright, Geoff (Advances in Social Sciences Research Journal, 2020)
The idea of the “flipped classroom” has become increasingly popular in education. However, very little research in how “flipped classrooms” impact high school students’ ability to perform on exams has been done. The purpose of this research is to add to the body of knowledge and help provide data to investigate how well students learn physics content by using the flipped classroom in a high school Physics with Technology class. Seven periods of Physics with Technology at Lone Peak High School in Highland, UT were used in this study. Three of the classes were randomly assigned to be “flipped” while the other four were taught using what is considered a “traditional” method of instruction of physics (guided inquiry). The pacing and content was matched each day and all classes participated in the same labs, homework, quizzes and tests. The defining difference is the method which the content was covered. The flipped classes watched video lectures at home to learn the majority of the content, then did what is traditionally known as “homework” in class with the teacher present to help. In this study, it was found that there was no statistically or practically significant difference in mean test scores for the first three units. Student responses on a survey also showed very little statistical difference in the students’ attitudes towards the classroom environment in either instructional method.